Dekonstruksi Pendidikan Seni Dalam Ruang Seni Anak Museum MACAN : Analisis Semiotika Roland Barthes - Tonce, Jessica Nathania; Ronda, Mirza; Napitupulu, Frengki (Magister of Communication Science, Sahid University Jakarta., 2021)
Art education has an important impact on the mental and physical development of students. Art education that has been available and open to the public is art learning that is obtained in the school environment or informal education related to drawing and sculpting. Museum MACAN (Modern and Contemporary Art in Nusantara) is present as the first art institution of its kind in Indonesia which constructs the concept of a museum to be more alive and relevant to society. Researchers try to see another side, namely how Museum MACAN interprets art education on its website. This research is a qualitative descriptive study using Roland Barthes' Semiotics method to analyze symbols that represent art education. Researchers also perceive art education deconstructed by Museum MACAN through its website. The results of this study indicate that there are other meanings regarding art education that are known to the public. Art education now has the meaning of free expression, using more sense of taste, and using the power of the mind to imagine